An endoxylanase rapidly hydrolyzes xylan into major product xylobiose via transglycosylation of xylose to xylotriose or xylotetraose. (1st June 2020) - Zheng, Fengzhen; Song, Lina; Basit, Abdul; Liu, Junquan; Miao, Ting; Wen, Jiaqi; Cao, Yunhe; Jiang, Wei
Graphical abstract: Highlights: Yield of the endoxylanase (Taxy11) from T. asperellum ND-1 was improved (68.40%). Glu 119, Glu 210, and Asp 53 were the essential catalytic sites for Taxy11 activity. A schematic model for Taxy11 shows novel catalysis mechanism in xylobiose production. Taxy11 efficiently converts corncob xylan into xylobiose-enriched XOSs (50.44%). Abstract: Here, we proposed an effective strategy to enhance a novel endoxylanase (Taxy11) activity and elucidated an efficient catalysis mechanism to produce xylooligosaccharides (XOSs). Codon optimization and recruitment of natural propeptide in Pichia pastoris resulted in achievement of Taxy11 activity to 1405.65 ± 51.24 U/mL. Analysis of action mode reveals that Taxy11 requires at least three xylose (xylotriose) residues for hydrolysis to yield xylobiose. Results of site-directed mutagenesis indicate that residues Glu 119, Glu 210, and Asp 53 of Taxy11 are key catalytic sites, while Asp 203 plays an auxiliary role. The novel mechanism whereby Taxy11 catalyzes conversion of xylan or XOSs into major product xylobiose involves transglycosylation of xylose to xylotriose or xylotetraose as substrate, to form xylotetraose or xylopentaose intermediate, respectively. Taxy11 displayed highly hydrolytic activity toward corncob xylan, producing 50.44 % of xylobiose within 0.5 h. This work provides a cost-effective and sustainable way to produce value-added biomolecules XOSs (xylobiose-enriched) from agricultural waste.